Music computer technologies in the perspective of digital humanities, arts, and researches - Gorbunova, Irina B. (Opción, 2019)
The article focuses on the active development of the Russian school of performing skills on electronic musical instruments (EMI) as one of the music computer technologies (MCT) forms. As a result, according to a significant part of the teachers surveyed, the use of EMI and MCT in childhood stimulates musical development and the ability to express oneself creatively and a desire to continue musical education. In conclusion, MCT and interactive network educational technologies are an excellent solution to the problems of teaching.